2022
DOI: 10.1136/bjo-2022-321985
|View full text |Cite
|
Sign up to set email alerts
|

Association of lipid-lowering drugs and antidiabetic drugs with age-related macular degeneration: a meta-analysis in Europeans

Abstract: Background/aimsTo investigate the association of commonly used systemic medications with prevalent age-related macular degeneration (AMD) in the general population.MethodsWe included 38 694 adults from 14 population-based and hospital-based studies from the European Eye Epidemiology consortium. We examined associations between the use of systemic medications and any prevalent AMD as well as any late AMD using multivariable logistic regression modelling per study and pooled results using random effects meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 74 publications
0
7
0
1
Order By: Relevance
“…In contrast, a very recently published meta-analysis by Mauschitz et al over 14 European population-or hospitalbased studies found a lower AMD prevalence in patients taking lipid-lowering and/or antidiabetic drugs (including metformin) (OR 0.78; 95% CI, p = 0.002) [47]. However, no association was found for late AMD stages (OR 1.12, 95% CI, p = 0.37).…”
Section: Effects Of Metformin Use On Amd In Retrospective Clinical Tr...mentioning
confidence: 89%
“…In contrast, a very recently published meta-analysis by Mauschitz et al over 14 European population-or hospitalbased studies found a lower AMD prevalence in patients taking lipid-lowering and/or antidiabetic drugs (including metformin) (OR 0.78; 95% CI, p = 0.002) [47]. However, no association was found for late AMD stages (OR 1.12, 95% CI, p = 0.37).…”
Section: Effects Of Metformin Use On Amd In Retrospective Clinical Tr...mentioning
confidence: 89%
“…Diskutiert wird z. B. ein positiver Effekt von Metformin 32 , 33 . Biologisch plausibel wäre dies, da Metformin antioxidative und antiinflammatorische Eigenschaften besitzt und oxidativen Stress im RPE reduzieren kann 34 .…”
Section: Risikofaktoren Für Amd Und Daraus Abzuleitende Potenzielle P...unclassified
“…Current epidemiological research is also concerned with the influence of long-term medication on the occurrence and progression of AMD in older patients. For example, a positive effect of metformin is under discussion 32 , 33 . Biologically, this would be plausible because metformin has antioxidant and anti-inflammatory properties and can reduce oxidative stress in the retinal pigment epithelium 34 .…”
Section: Risk Factors For Amd and Possible Prevention Measuresmentioning
confidence: 99%
“…A pooled data analysis of 38 694 people in Europe published in the British Journal of Ophthalmology found that drugs to lower cholesterol or control diabetes were associated with, respectively, a 15% and 22% lower prevalence of any type of age related macular degeneration (AMD), after accounting for potentially influential factors. The researchers said that longitudinal data would be needed to confirm the findings but that they pointed to a likely key role for metabolic processes in the development of AMD, which they said may offer potential new avenues for treatment and public health messaging 2…”
Section: Amdmentioning
confidence: 99%